BMC Cardiovascular Disorders
BMC Cardiovascular Disorders is an open access, peer-reviewed journal that considers articles on all aspects of the prevention, diagnosis and management of disorders of the heart and circulatory system, as well as related molecular and cell biology, genetics, pathophysiology, epidemiology, and controlled trials.